The Suffering Animal Life Between Weakness and Power - Ghelli, Simone (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book provides a critical and innovative reassessment of contemporary debate on the human-animal relationship. Starting with a critique of the "official philosophical narration" of animal studies, and then a reassessment of Descartes' animal-machine paradigm, Simone Ghelli tracks down the conceptual coordinates of what he calls "the paradigm of the suffering animal." The suffering animal is a materialist thesis on the condition of the living, which, while contesting the metaphysical and anthropocentric structure of western axiology, eventually redefines and re-establishes ethics on the experience of suffering, that is on the mutual compassion sentient beings feel before the unjust sight of their finitude. The suffering animal paradigm shows how, within our philosophical tradition, the animal question has been always intertwined with the questions of atheism and of materialism. The ultimate aim of this research is to define the "ethical equilibrium" between aspects of the living, such as weakness and power, joy and suffering, life and death, which our philosophical tradition largely tends to consider as mutually excluding. To overcome such oppositions means avoiding opposing, in our ethical and political discourse, the defense of the vulnerability of the weak and the freedom of the powerful. Simone Ghelli is a postdoctoral researcher at Scuola Normale Superiore di Pisa, Italy.
1 Introduction -- 1.1 An Animal Suffers for Nothing This Side of Good and Evil -- 1.2 Moderns Knew It: The Radical Challenge of the Suffering Animal -- 1.3 Life Is Weak -- 1.4 The Suffering Animal Faces the Extreme -- 1.5 Biodicies for Free Spirits -- 1.6 Luck of Some, Misfortune of All -- 1.7 Preliminary Notes -- Works Cited -- 2 The Sensitive Cogito: Modern Materialism and Its Legacy -- 2.1 A Shaky Canon -- 2.2 The Animal-Machine, or Rather Descartes' Dangerous Idea -- 2.3 The Rise of the Suffering Animal -- 2.4 The "Innovative Restoration" of the Rational Animal -- Works Cited -- 3 Life Is Overrated: On Darwin's Ultimate Materialism -- 3.1 The Evolution of the Suffering Animal -- 3.2 The Coral of Life and the Chance of Equality -- 3.3 The Revolt of Sentient Beings and the Chance of Civilization -- 3.4 There Is Life, Therefore God Cannot Exist -- 3.5 The Suffering Animal Versus the Powerful Animal -- Works Cited -- 4 Humanity as a Matter of Civilization: The Primo Levi Case -- 4.1 Thinking Dehumanization by Experience -- 4.2 The Inegalitarian God and Meaningless Suffering -- 4.3 The Salvation of Civilization -- 4.4 "We Weren't a Pleasant Sight" -- 4.5 The Salvation of Science -- Works Cited -- 5 The Rise of the Powerful Animal: On Deleuze's Materialism of Power -- 5.1 The Eclipse of the Suffering Animal -- 5.2 Releasing Life: Hume and Bergson -- 5.3 Releasing the Living: Spinoza and Nietzsche -- 5.4 Becoming the Powerful Animal that We Are -- 5.5 The Powerful Animal Reveals Their True Face -- Works Cited -- 6 Conclusion: The Powerful Animal Encounters the Suffering Animal -- Works Cited.
Keywords: Animal welfare -- Moral and ethical aspects; Ethics; Philosophy -- History; Animal Ethics; Moral Philosophy and Applied Ethics; History of Philosophy